PENARIKAN MINAT MASYARAKAT SEBAGAI WUJUD STRATEGI KEPALA SEKOLAH DALAM MEMBANGUN CITRA POSITIF LEMBAGA DI SMA WACHID HASYIM PAMEKASAN - Nurhadi, Ali; Angga Pratiwi, Novela; Soleh, Badrus (re-JIEM (Research Journal of Islamic Education Management), 2021)
The first step that parents take before entering their child into an educational institution is to choose the school of interest. To be able to attract the interest of the community, especially parents and prospective students in educational institutions, the school needs to make efforts to develop schools in order to maintain the image of the school in the community. Principals and teachers play an important role in this effort, especially the principal as a leader who carries out his leadership, namely regulating, managing all the resources of the educational institution he leads. Based on this, research was conducted at SMA Wachid Hasyim regarding the principal’s efforts to build a positive image of educational institutions to attract public interest, with two focuses, namely: 1) What is the principal’s strategy in building a positive image of educational institutions to attract public interest at SMA Wachid Hasyim Pamekasan; 2) What are the supporting and inhibiting factors for principals in building a positive image of educational institutions to attract public interest in Wachid Hasyim Pamekasan High School.